The significance of moral values embedded in English literature component short stories on form five students / Zulaikha Farhana Izehari - Izehari, Zulaikha Farhana (Faculty of Education, 2014)
Literature of English has become part of the component in KBSM syllabus in Malaysian education system and it serves to present moral contents aside from to teach language aspects. This study generally attempts to identify the variety of moral values prescribed in Form 4 English literature component short stories. The study also attempts to evaluate the reflection of prescribed moral values on students' personal characteristics and also to find students' perception towards the short stories QWERTYUIOP and The Fruitcake Special in their current syllabus. Questionnaires were distributed randomly to Form 5 students from Sekolah Seri Puteri, Cyberjaya. All the one hundred and nineteen respondents were from different levels of language proficiency and background. The instrument used for this study was questionnaire. The findings showed positive patterns which indicated that the short stories have portrayed relevant moral values and students are interested with the selected short stories. However, it was also found that students think that the selected short stories are not reflecting relevance to their religion or Malaysian culture. One of the major findings was students are able to comprehend the embedded moral values in their short stories. Another major finding was that most of the moral values embedded in the short stories are reflected in students' personal characteristics. In a conclusion, short stories benefits language learning from the linguistic aspects while posing advantages on moral development among students. Choosing relevant short stories that reflect the targeted moral values is important to mould morality through education of the following generations.